2018
DOI: 10.3389/fncel.2018.00177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Voluntary Wheel-Running Types on Hippocampal Neurogenesis and Spatial Cognition in Middle-Aged Mice

Abstract: While increasing evidence demonstrated that voluntary wheel running promotes cognitive function, little is known on how different types of voluntary wheel running affect cognitive function in elderly populations. We investigated the effects of various voluntary wheel-running types on adult hippocampal neurogenesis and spatial cognition in middle-aged mice. Male C57BL6 and Thy1-green fluorescent protein (GFP) transgenic mice (13 months) were equally assigned to one of the following groups: (1) T1: no voluntary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…On the other hand, published evidence has suggested that CUS significantly decreases cell proliferation in the neocortex in adult rats, and chronic antidepressant administration reverses the decrease in cortical cell proliferation (Banasr et al., 2007). Continuous voluntary wheel running significantly increases the number of BrdU + cells in the hippocampus of middle‐aged mice, and these new cells tend to differentiate into astrocytes (Huang et al., 2018). Similarly, voluntary exercise could increase astrocyte proliferation in the mPFC of control rats (Mandyam et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, published evidence has suggested that CUS significantly decreases cell proliferation in the neocortex in adult rats, and chronic antidepressant administration reverses the decrease in cortical cell proliferation (Banasr et al., 2007). Continuous voluntary wheel running significantly increases the number of BrdU + cells in the hippocampus of middle‐aged mice, and these new cells tend to differentiate into astrocytes (Huang et al., 2018). Similarly, voluntary exercise could increase astrocyte proliferation in the mPFC of control rats (Mandyam et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models enable the study of the microscopic changes in brain structure that support exercise-mediated cognitive benefits, such as the formation of new neurons (neurogenesis) and synapses (synaptogenesis) in the hippocampus. One of the strongest and earliest links between exercise and cognition was found on neurogenesis [75][76][77], which was 1 of the first hypotheses used to explain the neurobiological underpinnings of exercise-mediated cognitive performance benefits. However, when considering the generalizability of these microscopic findings to translational research in aging humans, it is pertinent to also consider how age might impact processes such as neurogenesis and synaptogenesis.…”
Section: Neurogenesis and Synaptogenesismentioning
confidence: 99%
“…It is well known that long-term voluntary running improves learning and memory, by enchancing the strength of neuronal connections, through synaptic plasticity in the hippocampus [ 78 , 79 ], and increasing neurogenesis [ 55 , 80 ]. Continuous voluntary wheel running exercise also contributes to astrogenesis and the repopulation of microglia [ 81 ]. The voluntary running-enhanced plasticity seems to be mediated by the Notch1 signaling pathway [ 82 ] and brain-specific angiogenesis inhibitor 1 (BAI1) [ 83 ].…”
Section: Running Experiencing Novelty and Mastication To Learn Faster...mentioning
confidence: 99%